Industrialization Without National Patents : The Netherlands, 1869-1912; Switzerland, 1850-1907 - Schiff, Eric, 1901- (Book collections on Project MUSE., 1971)
Eric Schiff analyzes two countries, widely known for their sophisticated industrial development, that are unique in having had no national patent protection for appreciable periods in their recent history. Originally published in 1971. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library.